2018
DOI: 10.1101/506246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA sequencing identifies dysregulated circular RNAs in early-stage breast cancer

Abstract: Background: Breast cancer is a major cause of cancer related death in women worldwide.Molecular diagnostic markers that are detectable in early-stage breast cancer can aid in effective clinical intervention. Circular RNAs are a recently identified group of non-coding RNA with potential role in cancer development and progression. In this study, we aimed to identify circular RNAs specific for early stage breast cancer. Method: Circular RNA expression profile was analyzed in early-stage breast cancer tissues (N=5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In addition, increasing numbers of evidences and studies have shown that circRNAs play significant roles in disease diagnosis and treatment 13. Especially for various cancers 14, 15, cardiovascular disease 16, diabetes 17, etc. Current researches of the associations between circRNAs and diseases are relatively advanced works, which might be based on the pathway circRNA-miRNA-mRNA to explore potential knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increasing numbers of evidences and studies have shown that circRNAs play significant roles in disease diagnosis and treatment 13. Especially for various cancers 14, 15, cardiovascular disease 16, diabetes 17, etc. Current researches of the associations between circRNAs and diseases are relatively advanced works, which might be based on the pathway circRNA-miRNA-mRNA to explore potential knowledge.…”
Section: Introductionmentioning
confidence: 99%